Interactive Narratives: Adapting Chinua Achebe’s Things Fall Apart into an Educational Video Game The Case Study of Third-Year Bachelor’s students at Mohamed Cherif Messaadia University Souk-Ahras - Rania HADDAD (My University, 2025)
Abstract This study aims to enhance the literature learning experience of third-year undergraduate students at Mohamed Cherif Messaadia University in Souk-Ahras by integrating video games into the teaching of Chinua Achebe’s Things Fall Apart. In response to the cognitive and linguistic challenges students face when engaging with complex literary texts, the study proposes the design and implementation of educational video games based on key elements of the novel. These gamified tasks seek to transform traditional instruction into a dynamic, student-centred experience that promotes deeper engagement, improves interpretive and problem-solving skills, and boosts motivation. Using a mixed-methods research design, the study combines qualitative and quantitative approaches through a semi-structured survey, non-participant classroom observation, and group discussions to assess students’ academic progress, engagement, and perceptions. Data is analysed through statistical tools and thematic analysis to evaluate the impact of gamified learning. Findings are expected to show that video game integration not only enhances academic performance but also fosters more positive attitudes toward literature. The study concludes that gamification can provide practical benefits for literature pedagogy by making learning more interactive, accessible, and enjoyable, ultimately supporting students in better understanding and appreciating complex literary works. ------------------ ملخص تهدف هذه الدراسة الى تعزيز تجربة تعلم الأدب لدى طلبة السنة الثالثة ليسانس بجامعة محمد الشريف مساعدية بسوق أهراس من خلال دمج ألعاب الفيديو في تدريس رواية الأشياء تتداعى لتشنوا أتشيبي. واستجابةً للتحديات المعرفية واللغوية التي يواجهها الطلبة عند التعامل مع النصوص الأدبية المعقدة، تقترح الدراسة تصميم وتنفيذ ألعاب فيديو تعليمية مبنية على عناصر أساسية من الرواية. تهدف هذه المهام المُعتمدة على التلعيب إلى تحويل التعليم التقليدي إلى تجربة ديناميكية تتمحور حول الطالب، تعزز التفاعل العميق، وتطُور مهارات التفسير وحل المشكلات، وتزيد من الدافعية. تعتمد الدراسة على تصميم بحثي بمنهجية مختلطة تجمع بين الطريقتين الكمية والنوعية، وذلك من خلال استبيان شبه موجه، وملاحظة صفية غير مشاركة، ونقاشات جماعية لتقييم التقدم الأكاديمي، ودرجة التفاعل، وانطباعات الطلبة. تحُلل البيانات باستخدام أدوات إحصائية وتحليل موضوعاتي لتقييم أثر التلعيب على التعلم. من المتوقع أن تظُهر النتائج أندمج ألعاب الفيديو في حصص الأدب لا يُحسن الأداء الأكاديمي فقط، بل يُسهم أيضًا في تعزيز مواقف أكثر إيجابية تجاه الأدب. و تخلص الدراسة إلى أن التلعيب يمكن أن يوفر فوائد عملية في تدريس الأدب من خلال جعل التعلم أكثر تفاعلاً وسهولة ومتعة، مما يُساعد الطلبة على فهم واستيعاب الأعمال الأدبية المعقدة بشكل أفضل. ------------------- Résume Cette étude vise à améliorer l’expérience d’apprentissage de la littérature chez les étudiants de troisième année de licence à l’Université Mohamed Cherif Messaadia de Souk-Ahras en intégrant les jeux vidéo dans l’enseignement de “Le monde s'effondre” de Chinua Achebe. En réponse aux défis cognitifs et linguistiques rencontrés par les étudiants face aux textes littéraires complexes, l’étude propose la conception et la mise en oeuvre de jeux vidéo éducatifs basés sur des éléments clés du roman. Ces tâches ludifiées visent à transformer l’enseignement traditionnel en une expérience dynamique centrée sur l’étudiant, favorisant un engagement plus profond, le développement des compétences interprétatives et de résolution de problèmes, et une motivation accrue. En adoptant une méthodologie de recherche mixte, l’étude combine des approches qualitatives et quantitatives à travers un questionnaire semi-structuré, une observation en classe non participante, et des discussions de groupe afin d’évaluer les progrès académiques, l’implication et les perceptions des étudiants. Les données sont analysées à l’aide d’outils statistiques et d’une analyse thématique pour évaluer l’impact de l’apprentissage ludifié. Les résultats attendus montrent que l’intégration des jeux vidéo dans les cours de littérature améliore non seulement les performances académiques, mais favorise également des attitudes plus positives envers la littérature. L’étude conclut que la ludification peut offrir des avantages pratiques pour la pédagogie littéraire en rendant l’apprentissage plus interactif, accessible et agréable, tout en aidant les étudiants à mieux comprendre et apprécier les oeuvres littéraires complexes
Keywords: Educational Video Games; Gamification; Gamified Learning; Literature Education; Things Fall Apart; Video Games.; الأدب، الألعاب التعليمية; التلعيب، التعليم عن طريق الألعاب ،الأشياء تتداعى ،ألعاب الفيديو; Apprentissage ludifié; Enseignement de la littérature; Jeux vidéo; Jeux vidéo éducatifs; Le monde s'effondre; Ludification